Edukasi Sosialisasi Mengenai KDRT Dan Dampak Pernikahan Dini Di Kelurahan Pandan Kasturi, Kota Ambon - Jusuf Leiwakabessy; Fidyana Fidyana; Yanti A. Lewerissa; ssy J. A. Hehanussa (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Arly marriage is a marriage carried out by someone who is relatively young. The relatively young age referred to is the age of puberty, namely between 10-19 years of age. One area in Indonesia, namely Pandan Kasturi sub-district, Sirimau District, Ambon City, Maluku Province, has a lot of early marriages. Early marriages that occur are caused by several factors and their impacts, one of which is domestic violence, domestic violence occurs because of selfish feelings between husband and wife, differences of opinion, not wanting to give in between husband and wife, wanting to win alone. and ended with domestic violence. Domestic violence occurs due to the mental and mental immaturity of each partner, so they do not really understand how to resolve the problems that occur in their household, so that the impact that occurs is physical, mental, psychological violence and so on. The aim of the community service implementation activity is to educate the importance of knowledge about domestic violence and early marriage in order to avoid or reduce domestic violence and early marriage in Pandan Kasturi Village.